Evaluasi Protokol Pengumpulan Bukti Forensik Dalam Kasus Pemerkosaan: Meningkatkan Kualitas Bukti dan Akurasi Identifikasi Pelaku - Muhammad Yusuf; Alpi Sahrin; Hudi Yusuf (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Handling rape cases requires effective forensic evidence collection to ensure justice for victims and truth disclosure in court. This study aims to evaluate protocols for collecting forensic evidence in rape cases, focusing on enhancing evidence quality and perpetrator identification accuracy. The evaluation method involves analyzing the implementation of existing protocols, including procedures for collecting and analyzing relevant physical, biological, and digital evidence in the context of sexual crimes. The study's findings indicate that increasing training and awareness of updated protocols can significantly improve the quality of collected evidence and the accuracy of perpetrator identification. These findings highlight the importance of collaboration among investigators, forensic experts, and other authorities in improving and implementing effective protocols for handling rape cases. This research provides a foundation for ongoing improvements in forensic procedures to enhance justice for victims of sexual crimes and overall community safety.